Benchmarking digitaler Gebrauchtgütermärkte - Eine Analyse zur Entwicklung von Best Practices am Beispiel von Miele Professional - Schröder, Felix

„For developers, by developers”? – Analyzing the Impact of Programming Languages’ Major Releases on Online Q&A Behavior - Werner, Timur

Interfacial Covalent Bonds Regulated Electron-Deficient 2D Black Phosphorus for Electrocatalytic Oxygen Reactions - Wang, Xia; Kormath Madam Raghupathy, Ramya; Querebillo, Christine Joy; Liao, Zhongquan; Li, Dongqi; Lin, Kui; Hantusch, Martin; Sofer, Zdeněk; Li, Baohua; Zschech, Ehrenfried; Weidinger, Inez M.; Kühne, Thomas; et al. (Advanced Materials)
Abstract Developing resource-abundant and sustainable metal-free bifunctional oxygen electrocatalysts is essential for the practical application of zinc–air batteries (ZABs). 2D black phosphorus (BP) with fully exposed atoms and active lone pair electrons can be promising for oxygen electrocatalysts, which, however, suffers from low catalytic activity and poor electrochemical stability. Herein, guided by density functional theory (DFT) calculations, an efficient metal-free electrocatalyst is demonstrated via covalently bonding BP nanosheets with graphitic carbon nitride (denoted BP-CN-c). The polarized PN covalent bonds in BP-CN-c can efficiently regulate the electron transfer from BP to graphitic carbon nitride and significantly promote the OOH* adsorption on phosphorus atoms. Impressively, the oxygen evolution reaction performance of BP-CN-c (overpotential of 350 mV at 10 mA cm−2, 90% retention after 10 h operation) represents the state-of-the-art among the reported BP-based metal-free catalysts. Additionally, BP-CN-c exhibits a small half-wave overpotential of 390 mV for oxygen reduction reaction, representing the first bifunctional BP-based metal-free oxygen catalyst. Moreover, ZABs are assembled incorporating BP-CN-c cathodes, delivering a substantially higher peak power density (168.3 mW cm−2) than the Pt/C+RuO2-based ZABs (101.3 mW cm−2). The acquired insights into interfacial covalent bonds pave the way for the rational design of new and affordable metal-free catalysts.
Keywords: 2D materials; bifunctional oxygen electrocatalysts; black phosphorus; oxygen evolution reaction; zinc–air batteries

Thermodynamically stable polymorphs of nitrogen-rich carbon nitrides: a C3N5 study - Ghasemi, Alireza; Mirhosseini, Hossein; Kühne, Thomas (Phys. Chem. Chem. Phys.)
We have carried out an extensive search for stable polymorphs of carbon nitride with C3N5 stoichiometry using the minima hopping method. Contrary to the widely held opinion that stacked{,} planar{,} graphite-like structures are energetically the most stable carbon nitride polymorphs for various nitrogen contents{,} we find that this does not apply for nitrogen-rich materials owing to the high abundance of N–N bonds. In fact{,} our results disclose novel morphologies with moieties not previously considered for C3N5. We demonstrate that nitrogen-rich compounds crystallize in a large variety of different structures due to particular characteristics of their energy landscapes. The newly found low-energy structures of C3N5 have band gaps within good agreement with the values measured in experimental studies.

Ein feministischer Blick: Zur Darstellung der Coronakrise in ausgewählter Kinder- und Jugendliteratur - Tönsing, Johanna (Mitteilungen des deutschen Germanistenverbands 2 (2021). In Krisen erzählen - von Krisen erzählen. Sprachliche, literarische und mediale Dimensionen)

External Focus of Attention Influences Cortical Activity Associated with Single Limb Balance Performance - Sherman, David A; Lehmann, Tim; Baumeister, Jochen; Gokeler, Alli; Donovan, Luke; Norte, Grant E (Physical Therapy)
Abstract Objective External focus (EF) of attention leads to improved balance performance. Consideration of the neuromodulatory effects of EF may inform its clinical utility in addressing neuroplastic impairments after musculoskeletal injuries. We aimed to determine whether electrocortical activity and balance performance changed with attentional foci that prioritized differing sensory feedback and whether changes in electrocortical activity and balance were associated. Methods Individuals who were healthy (n = 15) performed a single-limb balance task under 3 conditions: internal focus (IF), somatosensory focus [EF with a baton (EF-baton)], and visual focus [EF with a laser (EF-laser)]. Electrocortical activity and postural sway were recorded concurrently using electroencephalography and a triaxial force plate. Electroencephalographic signals were decomposed, localized, and clustered to generate power spectral density in θ and α-2 frequency bands. Postural sway signals were analyzed with center-of-pressure sway metrics (eg, area, distance, velocity) and knee angle. The relationship between percent change in clustered brain activity and task performance metrics was assessed. Results Both EF conditions resulted in increased cortical activity and improved balance performance compared to IF. EF-laser had the largest effect, demonstrating increased frontal θ power (d = 0.64), decreased central θ power (d = −0.30), and decreased bilateral motor, bilateral parietal, and occipital α-2 power (d = −1.38 to −4.27) as well as a shorter path distance (d = −0.94) and a deeper (d = 0.70) and less variable (d = −1.15) knee angle than IF. Weak to moderate associations exist between increases in cortical activity and improved balance performance (ρ = 0.405–0.584). Conclusions EF resulted in increased cortical activity associated with cognitive, motor, somatosensory, and visual processing. EF-laser, which prioritized visual feedback, had the largest and broadest effects. Changes in cortical activity resulting from EF were independently associated with improved balance performance. Impact This study demonstrates that goal-oriented attention results in functional increases in brain activity compared to internally directed self-focus. These results suggest EF may target neurophysiologic impairments and improve balance in clinical populations.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation

Light-responsive polymeric nanoparticles based on a novel nitropiperonal based polyester as drug delivery systems for photosensitizers in PDT - Schoppa, Timo; Jung, Dimitri; Rust, Tarik; Mulac, Dennis; Kuckling, Dirk; Langer, Klaus (International Journal of Pharmaceutics)

Backbone-Degradable (Co-)Polymers for Light-Triggered Drug Delivery - Rust, Tarik; Jung, Dimitri; Hoppe, Axel; Schoppa, Timo; Langer, Klaus; Kuckling, Dirk (ACS Applied Polymer Materials)

Direct Asymmetric Aldol Reaction in Continuous Flow Using Gel‐Bound Organocatalysts - Schmiegel, Carsten J.; Baier, Rene; Kuckling, Dirk (European Journal of Organic Chemistry)

Altering of lower critical solution temperature of environmentally responsive poly (N-isopropylacrylamide-co-acrylic acid-co-vanillin acrylate) affected by acrylic acid, vanillin acrylate, and post-polymerization modification - Abdelaty, Momen S. A.; Kuckling, Dirk (Colloid and Polymer Science)
Keywords: Materials Chemistry; Colloid and Surface Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry

Coupling of CO2 and epoxides catalysed by novel N-fused mesoionic carbene complexes of nickel(ii) - Watt, Fabian A.; Sieland, Benedikt; Dickmann, Nicole; Schoch, Roland; Herbst-Irmer, Regine; Ott, Holger; Paradies, Jan; Kuckling, Dirk; Hohloch, Stephan (Dalton Transactions)
Keywords: Inorganic Chemistry

Continuous Flow Synthesis of Azoxybenzenes by Reductive Dimerization of Nitrosobenzenes with Gel‐Bound Catalysts - Schmiegel, Carsten J.; Berg, Patrik; Obst, Franziska; Schoch, Roland; Appelhans, Dietmar; Kuckling, Dirk (European Journal of Organic Chemistry)

Backbone vs. side-chain: two light-degradable polyurethanes based on 6-nitropiperonal - Jung, Dimitri; Rust, Tarik; Völlmecke, Katharina; Schoppa, Timo; Langer, Klaus; Kuckling, Dirk (Polymer Chemistry)

Dually cross-linked single networks: structures and applications - Rodin, Maksim; Li, Jie; Kuckling, Dirk (Chemical Society Reviews)

Socio-legal systems and implementation of the Nash solution in Debreu–Hurwicz equilibrium - Haake, Claus-Jochen; Trockel, Walter (Review of Economic Design)
Abstract In this article we combine Debreu’s (Proc Natl Acad Sci 38(10):886–893, 1952) social system with Hurwicz’s (Econ Design 1(1):1–14, 1994; Am Econ Rev 98(3):577–585, 2008) ideas of embedding a “desired” game form into a “natural” game form that includes all feasible behavior, even if it is “illegal” according to the desired form. For the resulting socio-legal system we extend Debreu’s concepts of a social system and its social equilibria to a socio-legal system with its Debreu–Hurwicz equilibria. We build on a more general version of social equilibrium due to Shafer and Sonnenschein (J Math Econ 2(3):345–348, 1975) that also generalizes the dc-mechanism of Koray and Yildiz (J Econ Theory 176:479–502, 2018) which relates implementation via mechanisms with implementation via rights structures as introduced by Sertel (Designing rights: invisible hand theorems, covering and membership. Tech. rep. Mimeo, Bogazici University, 2001). In the second part we apply and illustrate these new concepts via an application in the narrow welfarist framework of two person cooperative bargaining. There we provide in a socio-legal system based on Nash’s demand game an implementation of the Nash bargaining solution in Debreu–Hurwicz equilibrium.

Beep-And-Sleep: Message and Energy Efficient Set Cover - Götte, Thorsten; Kolb, Christina; Scheideler, Christian; Werthmann, Julian (Algorithms for Sensor Systems (ALGOSENSORS '21))

Women Philosophers from the Renaissance to the Enlightenment
This collection of essays presents new work on women’s contribution to philosophy between the Renaissance and the mid-eighteenth century. They bring a new perspective to the history of philosophy, by highlighting women’s contributions to philosophy and testifying to the rich history of women’s thought in this period. By showing that women were active in many branches of philosophy (metaphysics, science, political philosophy cosmology, ontology, epistemology) the book testifies to the rich history of women’s thought across Europe in this period. The scope of the collection is international, both in terms of the philosophers represented and the contributors themselves from Britain and North America, but also from continental Europe and from as far afield as Australia and Brazil. The philosophers discussed here include both figures who have recently come to be better known (Elisabeth of Bohemia, Anne Conway, Mary Astell, Catharine Trotter Cockburn, Emilie du Châtelet), and less familiar figures (Moderata Fonte, Lucrezia Marinella Arcangela Tarabotti, Tullia d’Aragona, Madame Deshoulières, Madame de Sablé, Angélique de Saint-Jean Arnauld d’Andilly, Olivia Sabuco, Susanna Newcome). The chapters in this book were originally published as a special issue of the British Journal for the History of Philosophy.
Keywords: History of Women Philosophers; Methodology; History of Philosophy; Women's Studies; Gender History

Mixed‐Valence Compounds as Polarizing Agents for Overhauser Dynamic Nuclear Polarization in Solids - Gurinov, Andrei; Sieland, Benedikt; Kuzhelev, Andrey; Elgabarty, Hossam; Kühne, Thomas; Prisner, Thomas; Paradies, Jan; Baldus, Marc; Ivanov, Konstantin L.; Pylaeva, Svetlana (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

An Exploratory Meta-Analytic Review on the Empirical Evidence of Differential Learning as an Enhanced Motor Learning Method - Tassignon, Bruno; Verschueren, Jo; Baeyens, Jean-Pierre; Benjaminse, Anne; Gokeler, Alli; Serrien, Ben; Clijsen, Ron (Frontiers in Psychology)
Background: Differential learning (DL) is a motor learning method characterized by high amounts of variability during practice and is claimed to provide the learner with a higher learning rate than other methods. However, some controversy surrounds DL theory, and to date, no overview exists that compares the effects of DL to other motor learning methods. Objective: To evaluate the effectiveness of DL in comparison to other motor learning methods in the acquisition and retention phase. Design: Systematic review and exploratory meta-analysis. Methods: PubMed (MEDLINE), Web of Science, and Google Scholar were searched until February 3, 2020. To be included, (1) studies had to be experiments where the DL group was compared to a control group engaged in a different motor learning method (lack of practice was not eligible), (2) studies had to describe the effects on one or more measures of performance in a skill or movement task, and (3) the study report had to be published as a full paper in a journal or as a book chapter. Results: Twenty-seven studies encompassing 31 experiments were included. Overall heterogeneity for the acquisition phase (post-pre; I 2 = 77%) as well as for the retention phase (retention-pre; I 2 = 79%) was large, and risk of bias was high. The meta-analysis showed an overall small effect size of 0.26 [0.10, 0.42] in the acquisition phase for participants in the DL group compared to other motor learning methods. In the retention phase, an overall medium effect size of 0.61 [0.30, 0.91] was observed for participants in the DL group compared to other motor learning methods. Discussion/Conclusion: Given the large amount of heterogeneity, limited number of studies, low sample sizes, low statistical power, possible publication bias, and high risk of bias in general, inferences about the effectiveness of DL would be premature. Even though DL shows potential to result in greater average improvements between pre- and post/retention test compared to non-variability-based motor learning methods, more high-quality research is needed before issuing such a statement. For robust comparisons on the relative effectiveness of DL to different variability-based motor learning methods, scarce and inconclusive evidence was found.
Keywords: General Psychology

High Incidence of Anterior Cruciate Ligament Injuries Within the First 2 Months of the Season in Amateur Team Ball Sports - Mouton, Caroline; Gokeler, Alli; Urhausen, Anouk; Nührenbörger, Christian; Seil, Romain (Sports Health: A Multidisciplinary Approach)
Background: The incidence of anterior cruciate ligament (ACL) injuries is commonly reported as an annual incidence rate. There is relatively little information about the seasonal aspects of these injuries. The aim of the current study was to analyze the distribution of ACL injuries during the season in nonprofessional soccer, handball, and basketball based on a retrospective analysis of a hospital-based registry. Hypothesis: ACL injuries in soccer, handball, and basketball were more common within the first 2 months of the season in comparison with the rest of the year. Study Design: Case series. Level of Evidence: Level 4. Methods: Injury occurrence during the calendar year was divided into 6 periods of 2 months, with segment 1 (S1) representing the first 2 months of the season. For soccer, S1 corresponded to September and October. The season started 1 month later for handball and basketball, so S1 represented October and November. Chi-square tests were used to analyze the distribution of ACL injuries among segments according to gender, age, sports, and injury mechanism (contact/noncontact). Results: A total of 371 ACL injuries were included (soccer, 258, handball, 56, basketball, 57). Overall, the distribution of ACL injuries was not uniform across the segments ( P < 0.01). Almost one-third of the ACL injuries occurred in S1 (n = 104; 28%). Significant differences could be observed according to sports ( P < 0.01). There were fewer ACL injuries in S2 for soccer compared with basketball ( P < 0.05). In S5, there were significantly more ACL injuries in soccer compared with handball and basketball ( P < 0.05). Conclusion: A high occurrence of ACL injuries was reported immediately within the first 2 months of the season in nonprofessional soccer, handball, and basketball sports. Clinical Relevance: These findings indicate that ACL injury prevention programs should be started in the preseason period to allow for gradual increases of load.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine